Population growth, movements, and status of the Nushagak Peninsula Caribou Herd following reintroduction, 1988 - 2000 - Collins, Gail H.; Hinkes, Michael T.; Aderman, Andrew R.; Woolington, James D. (Rangifer, 2003)
Barren ground caribou (Rangifer tarandus) were reintroduced to the Nushagak Peninsula, Alaska in February of 1988 after an absence of more than 100 years. Since reintroduction, herd growth and population dynamics have been monitored closely. At this time, there has been no significant dispersal from the herds' core range. The Nushagak Peninsula Caribou Herd (NPCH) grew rapidly from 146 reintroduced individuals to over 1000 in 13 years. Dramatic mean annual growth during the first 6 years (1988-1994) of 38% (r = 0.32) can be attributed to the high percentage of females in the initial reintroduction, high calf production and survival, exceptional range conditions, few predators, and no hunting. However, the populations' exceptional growth (peak counts of 1400) slowed and stabilized between 1996¬1998 and then decreased between 1998 and 2000. Size, body condition and weights of calves captured in 2000 were significantly lower than those captured in 1995 and 1997. Although calf production also decreased from close to 100% (1990-1995) to about 91% (1996-2000), overall calf survival continued to be high. Legal harvest began in 1995, and harvest reports have accounted for approximately 3% of population mortality annually. Although brown bears (Ursus arctos) and wolves (Canis lupus) are present, the extent of predation is unknown. Mean home range of the NPCH was 674 km2 and group sizes were greatest during post-calving aggregation in July (mean = 127). Caribou population density on the Nushagak Peninsula reached approximately 1.2 caribou/km2 in 1997 before declining to about 1.0 caribou/km2. A range survey in 1994 noted only trace utilization of lichens on the Nushagak Peninsula by caribou. A subsequent survey in 1999 found moderate to severe utilization in 46% of plots, suggesting the reintroduced herd was beginning to alter range condition. Between 1997 and 2000, both calf production and condition of 10-month-old calves declined. Calving has also been delayed in recent years. However, we suspect the reduced herd growth can be attributed to increasing hunting pressure and some dispersal of caribou from the Peninsula, not reduced range condition.